Irregular Migration as a Potential Source of Malaria Reintroduction in Sri Lanka and Use of Malaria Rapid Diagnostic Tests at Point-of-Entry Screening. (18th June 2013) - Wickramage, Kolitha; Galappaththy, Gawrie N. L.; Dayarathne, D.; Peiris, Sharika L.; Basnayake, Rajeeka N.; Mosca, Davide; Jacobs, Jan
Abstract : Background . We describe an irregular migrant who returned to Sri Lanka after a failed people smuggling operation from West Africa. Results . On-arrival screening by Anti-Malaria Campaign (AMC) officers using a rapid diagnostic test (RDT) (CareStart Malaria HRP2/PLDH) indicated a negative result. On day 3 after arrival, he presented with fever and chills but was managed as dengue (which is hyperendemic in Sri Lanka). Only on day 7, diagnosis of Plasmodium falciparum malaria was made by microcopy and CareStart RDT. The initially negative RDT was ascribed to a low parasite density. Irregular migration may be an unrecognized source of malaria reintroduction. Despite some limitations in detection, RDTs form an important point-of-entry assessment. As a consequence of this case, the AMC is now focused on repeat testing and close monitoring of all irregular migrants from malaria-endemic zones. Conclusion . The present case study highlights the effective collaboration and coordination between inter-governmental agencies such as IOM and the Ministry of Health towards the goals of malaria elimination in Sri Lanka.